Actual pressure generated by various suction technique and suctioning liquid weight through endoscopic ultrasound‐guided aspiration needles. Issue 12 (21st February 2023) - Sheng, Li Ping; Lin, Rong; Tao, Xu; Guo, Xian Wen; Han, Chao Qun; Nie, Chi; Zhang, Kun; Ding, Zhen
Abstract : Objectives: Suction pressure is one of the most important factors influencing the amount of tissue obtained during endoscopic ultrasound‐guided fine‐needle aspiration/biopsy (EUS‐FNA/FNB). In this study we aimed to elucidate actual suction pressure generated by various suction methods and the weight of suctioning liquid. Methods: Different types of fine needles and suction techniques were used, including the slow pull technique (SPT), dry suction technique (DST), wet suction technique (WST), neutralizing negative pressure technique (NNPT), and residual negative pressure technique (RNPT). Actual suction pressure was measured and the amount of suctioning liquid was weighed. Results: Actual suction pressure and weight of the suctioning liquid were lower using SPT than using DST, while they were higher when using WST compared with those using DST. In general, the actual suction pressure increased and the weight of suctioning liquid decreased as the diameter of the FNA needles decreased. While weight of the suctioning liquid using FNB needles was significantly larger than that using FNA needles. In general, the actual suction pressure generated using RNPT was larger than that using NNPT. Conclusions: WST is superior to SPT and DST in terms of actual suction pressure and weight of suctioning liquid. Diameter of the FNA needle was an important factor that may affect the actual suction pressure and weight of suctioning liquid. FNB needles are superior to FNA needles when it comes to the weight of suctioning liquid. Actual suction pressure obtained by novel suction methods (NNPT and RNPT) may provide a basis for future research. Abstract : Needle pressure measured by A, setup using various suction methods other than the slow pull technique (SPT), and B, setup using SPT